2006
DOI: 10.1002/chem.200501088
|View full text |Cite
|
Sign up to set email alerts
|

Gold(I)‐Catalyzed Cyclizations of 1,6‐Enynes: Alkoxycyclizations and exo/endo Skeletal Rearrangements

Abstract: Gold(I) complexes are the most active catalysts for alkoxy- or hydroxycyclization and for skeletal rearrangement reactions of 1,6-enynes. Intramolecular alkoxycyclizations also proceed efficiently in the presence of gold(I) catalysts. The first examples of the skeletal rearrangement of enynes by the endocyclic cyclization pathway are also documented. Iron(III) is also able to catalyze exo and endo skeletal rearrangements of 1,6-enynes, although the scope of this transformation is more limited. The gold(I)-cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
242
0
7

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 376 publications
(263 citation statements)
references
References 102 publications
14
242
0
7
Order By: Relevance
“…[11,28] The minor product 162 corresponded to the expected cycloisomerization process, which was discussed above. The major product, however, was determined to be methylenecyclohexene 161, corresponding to a new reaction manifold.…”
Section: Conversion Of 16-enynes To Methylenecyclohexenesmentioning
confidence: 96%
See 1 more Smart Citation
“…[11,28] The minor product 162 corresponded to the expected cycloisomerization process, which was discussed above. The major product, however, was determined to be methylenecyclohexene 161, corresponding to a new reaction manifold.…”
Section: Conversion Of 16-enynes To Methylenecyclohexenesmentioning
confidence: 96%
“…In 2004, as a part of their comprehensive study of gold-based catalysis of enyne cycloisomerizations, Echavarren and co-workers reported that cationic gold complexes were exceedingly effective in promoting alkoxycarbocyclizations of a wide range of 1,6-enynes. [11,28] A representative scope of this process, as well as the typical reaction conditions, is shown in Scheme 27.…”
Section: Formation Of Alkyl-and Alkenylmethylenecyclopentanes and Cycmentioning
confidence: 99%
“…[168] Malacria et al [132] hatten schon früher die Reaktivität von Eninamiden in Gegenwart von Platin untersucht und eine ähnliche Reaktivität festgestellt, wenn auch bei höherer Temperatur [siehe Gl. [149,150,173] oder auf Gold(III)-Vorstufen [115,174] [Gl. (152) + zu erzeugen.…”
Section: Enin-tandemreaktionenunclassified
“…[8] The similarity be- tween KITPHOS and Buchwalds biaryl monophosphines, combined with the fact that the latter have proven to be very successful ligands for a vast array of gold-catalysed transformations [9] prompted us to synthesise gold complexes of these KITPHOS monophosphines and investigate their applications in a selection of gold-catalysed cycloisomerisations.…”
mentioning
confidence: 99%